Biomethanation of Syngas Using Anaerobic Sludge: Shift in the Catabolic Routes with the CO Partial Pressure Increase - Sancho Navarro, Silvia; Cimpoia, Ruxandra; Bruant, Guillaume; Guiot, Serge R. (Frontiers in Microbiology, 2016)
Syngas generated by thermal gasification of biomass or coal can be steam reformed and purified into methane, which could be used locally for energy needs, or re-injected in the natural gas grid. As an alternative to chemical catalysis, the main components of the syngas (CO, CO2, and H2) can be used as substrates by a wide range of microorganisms, to be converted into gas biofuels, including methane. This study evaluates the carboxydotrophic (CO-consuming) methanogenic potential present in an anaerobic sludge from an upflow anaerobic sludge bed (UASB) reactor treating waste water, and elucidates the CO conversion routes to methane at 35±3˚C. Kinetic activity tests under CO at partial pressures (pCO) varying from 0.1 to 1.5 atm (0.09-1.31 mmol/L in the liquid phase) showed a significant carboxydotrophic activity potential for growing conditions on CO alone. A maximum methanogenic activity of 1 mmol CH4 per g of volatile suspended solid and per day was achieved at 0.2 atm of CO (0.17 mmol/L), and then the rate decreased with the amount of CO supplied. The intermediary metabolites such as acetate, H2 and propionate started to accumulate at higher CO concentrations. Inhibition experiments with 2-bromoethanesulfonic acid (BES), fluoroacetate, and vancomycin showed that in a mixed culture CO was converted mainly to acetate by acetogenic bacteria, which was further transformed to methane by acetoclastic methanogens, while direct methanogenic CO conversion was negligible. Methanogenesis was totally blocked at high pCO in the bottles (≥ 1 atm). However it was possible to achieve higher methanogenic potential under a 100% CO atmosphere after acclimation of the sludge to CO. This adaptation to high CO concentrations led to a shift in the archaeal population, then dominated by hydrogen-utilizing methanogens, which were able to take over acetoclastic methanogens, while syntrophic acetate oxidizing (SAO) bacteria oxidized acetate into CO2 and H2. The disaggregation of the granular sludge showed a negative impact on their methanogenic activity, confirming that the acetoclastic methanogens were the most sensitive to CO, and a contrario, the advantage of using granular sludge for further development towards large-scale methane production from CO-rich syngas.